Constraints faced by women entrepreneurs in developing countries: review and ranking. Issue 4 (3rd April 2018) - Panda, Swati
Abstract : Purpose: This paper aims to identify and ranks constraints faced by women entrepreneurs in developing countries. It offers a framework to differentiate between the constraints faced by male and female entrepreneurs. Design/methodology/approach: The paper engages in an exhaustive literature review and uses a qualitative methodology to categorize and rank entrepreneurial constraints. Findings: Constraints faced by women entrepreneurs in developing countries arise from gender discrimination, work-family conflict, difficulty in raising capital, lack of infrastructure, unstable business, economic and political (BEP) environments, lack of training and education and personality differences. The study suggests that in addition to financial constraints, unstable BEP environments need to be addressed as top priorities. Originality/value: This study offers a broad overview and ranking of the constraints faced by women entrepreneurs in developing countries. It brings together literature on women entrepreneurship from multiple countries and creates a condensed body of knowledge. This paper bridges the gap between entrepreneurship theory and practice and gives direction to policy makers in creating a conducive environment for the success of women entrepreneurs.